Economic Analysis of Domestic Automated Forced Circulation Solar Water Heater - Mohammed Khoder; Abdelrouf Ibojilida; Ashabani Shleag; Eisay Almishraqi (African Journal of Advanced Pure and Applied Sciences, 2023)
Countries are currently facing the urgent need to tackle the climate crisis, reduce pollution, and protect our planet’s biodiversity and other natural resources, while simultaneously ensuring that a transition to a low-carbon greener economy delivers benefits to all. To meet environmental goals and be in line with Agenda 2030, policy- and decision-makers need to consider links between environmental policy responses and other goals. In this direction, economic analysis is carried out based on previous experimental data obtained for both conventional energy savings: electrical and oil fuel with MENA region. The results of energy savings and overall efficiencies of domestic automated forced circulation water heating. The analytical results obtained lead to several conclusions; the importance is: The combined solar and oil-fuel water heaters become economics after a period of usage (14 years) with a collector area of 10 i.e. becomes commercial and the percentage of energy saving under continuous constant load varies between 14% during the winter season and 75% during the spring season. The yearly economic analysis is based on 9 months omitting summer months as the collector efficiency will be higher than 100%. The correlation coefficient between this study’s results and other previous studies either with saved energies or payback periods approaches is clear that: correct data analysis, the precision of gathering experimental data and the assumptions were done.